Use of Platelet-Rich Plasma for Patellar Tendon and Medial Collateral Ligament Injuries: Best Current Clinical Practice - Andia, Isabel; Maffulli, Nicola (The Journal of Knee Surgery, 2015)
Platelet-rich plasmas (PRPs) are complex molecular therapies prepared from the patient's own blood through minimal manipulation. Clinical studies examining the efficacy of PRPs to manage patellar tendinopathy and medial collateral ligament (MCL) injuries have been reviewed. We found three controlled trials, two of them randomized, and seven case series in the management of patellar tendinopathy. In addition, three other randomized studies showed that PRPs help to regenerate the patellar tendon harvest site for anterior cruciate ligament reconstruction and to reduce patellar donor site morbidity. On the other hand, the use of PRP in MCL injuries is reported in a single case study. Seven of the 11 studies used leukocyte and PRP which was buffered in four studies. Seven of the 11 studies applied two or three injections. Given the heterogeneity of PRP protocols and the paucity of high-quality data, the most effective approach to guide clinical decisions regarding patellar tendinopathy cannot be deduced from the present published studies.
Keywords: tissue regeneration; signaling proteins; biological therapy